IMPLIKASI COVID-19 TERHADAP PELAKSANAAN BIMBINGAN DAN KONSELING DI KABUPATEN SAMBAS (CROSS-BORDER) - Patriana (Cross-border, 2020)
This study aims to obtain an overview of the implementation of guidance and counseling in school during the Covid-19 in Sambas District and to find out the difficulties in implementing guidance and counseling during the Covid-19 period in Sambas Districk in 2020. This Study Uses qualitative research methods with interview and observation techniques to 8 guidance and counseling teachers. The results showed that the implementation of guidance and counseling during the Covid period was ineffective because almost some school were only present in online without any services provided. In addition, although there are some counseling teachers who provide sercives online there are still many students who do not participate in these services. The difficulties in implementing guidance and counseling the Covid-19 period were a) limited mastery of information by teacher and students; b) don’t have a smartphone, c) limited internet access and d) students who lack discipline in the servise delivery process.